2007
DOI: 10.1038/sj.bjc.6603746
|View full text |Cite
|
Sign up to set email alerts
|

The future burden of cancer in England: incidence and numbers of new patients in 2020

Abstract: We estimated the future cancer incidence rates and the future numbers of cancer cases in England up to 2020 using cancer registration data for 1974 -2003, and the official population projections from ONS up to 2023. Data were analysed using an ageperiod-cohort model as developed for the Nordic countries. We predict that for all cancers combined there will be relatively little change in age-standardised incidence rates in 2020. The number of new cancer cases per year in England is, however, predicted to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 12 publications
2
71
0
8
Order By: Relevance
“…The results show an upward pattern and no sex-related differences in incidence for stomach and lung cancer, and also for all cancer combined with exception non melanoma skin cancers which reported previously (Maracy et al, 2012). Incidence trends in European countries is quietly associated with sex and rates in male are decreasing or reached a turning point while for females continue to rise (Grande et al, 2006;Moller et al, 2007;Sanchez et al, 2010). In this study, males and females displayed an increasing pattern for incidence and mortality rate over the entire study period by 2015.…”
Section: Discussionmentioning
confidence: 53%
“…The results show an upward pattern and no sex-related differences in incidence for stomach and lung cancer, and also for all cancer combined with exception non melanoma skin cancers which reported previously (Maracy et al, 2012). Incidence trends in European countries is quietly associated with sex and rates in male are decreasing or reached a turning point while for females continue to rise (Grande et al, 2006;Moller et al, 2007;Sanchez et al, 2010). In this study, males and females displayed an increasing pattern for incidence and mortality rate over the entire study period by 2015.…”
Section: Discussionmentioning
confidence: 53%
“…In this study, we used the 2006-based population projections prepared by the Government Actuary's Department. Møller et al (2007) carried out a similar analysis, using the same methodology, with respect to cancer incidence in England. In that study, 2004-based population projections were used.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evaluations of the prediction intervals have shown that caution should be taken when interpreting them (Møller et al (2005)). Further to this, there have been claims that these intervals should not be reported because they may be wrongly interpreted (Møller et al (2007)). …”
Section: Discussionmentioning
confidence: 99%
“…Of course, calculations can be made for the uncertainty for the parameters in a given model, and prediction intervals can be put on the estimated rates (Elkum (2005), Møller, Weedon-Fekjaer, and Haldorsen (2005)). However, these intervals can be very narrow in population-based cancer studies where lots of information is available (Møller et al 2007). The proposed prediction intervals do not take into account the bias introduced by making an untestable assumption about the future rates based on the available data.…”
Section: Discussionmentioning
confidence: 99%